Adult and continuing education in Cyprus - Gravani, Maria [Verfasser]; Ioannidou, Alexandra [Verfasser] (Bertelsmann, 2014)
"Der Band liefert eine aktuelle Bestandsaufnahme zu zentralen Bereichen der Weiterbildung in Zypern. Die Autorinnen haben vielfältige Daten und Informationen zu Institutionen, Finanzierung, Angeboten, Teilnahme, Personal, Qualitätssicherung und der Zertifizierung zusammengestellt. Darüber hinaus berücksichtigen sie auch den politischen, geopolitischen und kulturellen Kontext sowie die wirtschaftliche Situation der Insel Zypern. Dieses Buch vermittelt einen schnellen Einstieg sowie eine gute Orientierung über das System der Erwachsenen- bzw. Weiterbildung in Zypern." (Verlag, BIBB-Doku)

"This book gives an overview of central aspects of Adult Education and Training in Cyprus in an attempt to sketch out the country’s profile in the field. Based on empirical findings from a current research project, Maria Gravani and Alexandra Ioannidou present a range of data and information regarding the historical development of Adult and Continuing Eeducation in the island, the adult education and training institutions, financing, provision, participation, staff and professionalism, quality assurance and certification processes and current research conducted in the area of higher education. The authors describe Adult Education and Training in Cyprus taking into consideration the political, geopolitical, legal and cultural context as well as the current economic situation in the island. This book offers a brief and systematic introduction and good orientation in the system of Adult Education and Training in Cyprus." (Publisher, BIBB-Doku)
Keywords: S 1.5 Weiterbildung; I 2.2.2 Osteuropa; Weiterbildung; Erwachsenenbildung; Historische Entwicklung; Weiterbildungseinrichtung; Weiterbildungsfinanzierung; Weiterbildungsangebot; Weiterbildungsbeteiligung; Bildungspersonal; Weiterbildungsstatistik; Qualitätssicherung; Zypern